Peptide Dimerization as a Strategy for the Development of Antileishmanial Compounds - Natália C. S. Coelho; Deivys L. F. Portuondo; Jhonatan Lima; Angela M. A. Velásquez; Valéria Valente; Iracilda Z. Carlos; Eduardo M. Cilli; Márcia A. S. Graminha (Molecules)
Leishmaniasis is recognized as a serious public health problem in Brazil and around the world. The limited availability of drugs for treatment, added to the diversity of side effects and the emergence of resistant strains, shows the importance of research focused on the development of new molecules, thus contributing to treatments. Therefore, this work aimed to identify leishmanicidal compounds using a peptide dimerization strategy, as well as to understand their mechanisms of action. Herein, it was demonstrated that the dimerization of the peptide TSHa, (TSHa)2K, presented higher potency and selectivity than its monomeric form when evaluated against Leishmania mexicana and Leishmania amazonensis. Furthermore, these compounds are capable of inhibiting the parasite cysteine protease, an important target explored for the development of antileishmanial compounds, as well as to selectively interact with the parasite membranes, as demonstrated by flow cytometry, permeabilization, and fluorescence microscopy experiments. Based on this, the identified molecules are candidates for use in in vivo studies with animal models to combat leishmaniasis.